Endoscopic management of maxillary sinus inverted papilloma attachment sites to minimize disease recurrence - Wu, Vincent (J Otolaryngol Head Neck Surg, 2018)
BACKGROUND: Inverted papillomas (IPs) are benign neoplasms, most commonly arising from the mucosal lining of the maxillary sinus. IPs can have single or multifocal sites of attachment. Although pedicle location is an important factor to consider in surgical planning, it is less clear whether the location or number of IP attachment sites hold any prognostic value. Herein, we aimed to determine the prognostic significance of the number and location of attachment sites of IPs originating from the maxillary sinus when managed by a pure endoscopic approach. METHODS: This was a single-center, single-surgeon retrospective chart review. Patients with maxillary sinus IPs who were managed by endoscopic approaches only, from January 1, 2010 to June 30, 2016, were identified. Demographic data, operative technique, number and location of IP attachment sites, follow-up duration, recurrence, and presence of malignant transformation were captured. RESULTS: Twenty-eight maxillary IP patients (61% males) were included, with a mean age of 54.9 (standard deviation (SD): 16.5) years. Approximately 36% of patients were referred from other institutions for management of recurrent IPs after failing previous surgical treatment. All patients were managed with an endoscopic approach, and all required an endoscopic medial maxillectomy to facilitate access to the maxillary sinus. At a mean follow-up of 31.1 (SD: 22.6) months, there were no recurrences identified. IPs with single (46%) and multifocal (54%) attachments were predominately to the medial and lateral walls. Maxillary IPs with multifocal attachments most frequently involved 2-3 walls of the sinus. Osteitis (36%) was commonly seen. CONCLUSION: IPs originating from the maxillary sinus frequently had multifocal attachments, but this did not impact disease recurrence. Despite the surgical challenges of accessing all of the maxillary sinus walls, IPs originating from the maxillary sinus can be effectively managed via a pure endoscopic approach.